Penguatan Desain Dakwah Masjid di Era Milenilal melalui Android - Jasuri Jasuri; M. Ardhi Khalif; Edi Daenuri Anwar (LP2M of Institute for Research and Community Services - UIN Walisongo, 2019)
Dedication work with the title